Functional characterization of plant-based protein to determine its quality for food applications. (February 2022) - Kumar, Manoj; Tomar, Maharishi; Potkule, Jayashree; Reetu; Punia, Sneh; Dhakane-Lad, Jyoti; Singh, Surinder; Dhumal, Sangram; Chandra Pradhan, Prakash; Bhushan, Bharat; Anitha, T.; Alajil, Omar; et al.
Abstract: Protein plays a role as an indispensable macronutrient in human nutrition. The utilization of new protein sources from plants requires a thorough investigation for application in foods. Functional characterization is the most important step for the quality assessment of protein along with annotating the protein with a specific application in food systems. The evaluation of plant protein for quality and functional properties is critical in replacing conventional animal-based proteins. This review aims to discuss the important parameters considered crucial for the application of protein in foods. The amino acid profile is the most important parameter for the evaluation of the quality of a protein, while others (viz., molecular weight distribution, structural morphology, and thermal stability) are crucial properties of the protein. This review also focuses on various food functional properties (water/oil holding capacity, emulsification activity/stability, and solubility) and in vitro digestibility, which are considered important for identifying a distinct application for a particular plant protein. Research trends show numerous emerging sources of quality plant proteins, but their utilization as food supplements depends on their availability, safety, and consumer preferences. However, advancements in techniques for functional characterization could assist in exploring new plant protein sources that can be utilized in human nutrition. Graphical abstract: Image 1 Highlights: Plant-based proteins are assessed using various techniques as outlined in the review. Amino acid profile is considered most important among all quality parameters. Plant proteins are characterised based on surface morphology and thermal properties. Functional food properties are crucial for annotating application to plant protein.